Harmonic Poetics and Vocal Subtlety in Karambangan: Interpreting Pamona Musical Aesthetics - Setyawan, Dedi; Wibawa, Budi (Indonesian Scientific Publication, 2024)
Karambangan is a traditional vocal genre of the Pamona people in Central Sulawesi, Indonesia, blending poetic kayori with guitar based harmonic textures. This study aims to analyze the vocal interpretation strategies employed by Karambangan performers, focusing on the integration of harmony, diction, and vocal affect within cultural and pedagogical contexts. Using a multidisciplinary approach, the research combines ethnographic fieldwork, harmonic transcription, phonetic analysis, and cultural interpretation. Data were collected through audio recordings, kayori texts, and interviews with performers. Harmonic progressions were mapped, vocal timbre and vibrato were measured, and rhetorical features in lyrics were analyzed. Findings reveal that Karambangan vocalists emphasize emotional nuance through vibrato restraint, nasal resonant timbre, and precise prosodic alignment. Harmonic structures often based on three chord cycles and supported by alternate guitar tunings offer a stable platform for expressive delivery. Kayori lines are vocally interpreted through dynamic shaping, rhetorical timing, and culturally informed diction. The study also discusses the pedagogical value of these techniques and the ethical considerations of transitioning the genre from ritual to stage. Karambangan emerges as a genre of artistic and cultural significance, where voice serves not only as a musical tool but also as a moral and spiritual practice. The research contributes a genre specific model for vocal interpretation in indigenous traditions and highlights the importance of culturally embedded music education.